Modeling of a photovoltaic drip irrigation system for an offseason crop: case of onion cultivation in PITOA (North Cameroon) - Andre, Boussaibo; Alphonse, Sawalda; Ngasop Stephane, Ndjiya; Goron, Deli; Armel Duvalier, Pene; ., Kitmo (International Journal of Engineering and Technology, 2024)
In this article, attention is paid to the use of photovoltaic electricity for the popularization of off-season agriculture in arid Sahelian areas. Here we propose an efficient solar drip irrigation model for rational use of water for off-season crops. The model of the proposed sys-tem is developed in the MATALAB/Simulink environment. The results of simulations based on field data specific to the cultivation of off-season onions in the locality of PITOA (North Cameroon) are obtained for a cultivable area of 1 hectare, according that the area to be irrigated is 7200 m². The algorithm developed for determining the soil capacity made it possible to evaluate the useful reserve at 1.70 mm/cm. Under the set test conditions (temperature 25°C, irradiance 1000 W/m²), the water flow provided by a dripper is estimated at 20 l/h. To meet the water needs of crops, the power of the photovoltaic generator is 1600 W peak.